Inhibition by Thyroid Hormones of Cell Migration Activated by IGF-1 and MCP-1 in THP-1 Monocytes: Focus on Signal Transduction Events Proximal to Integrin αvβ3 - Candelotti, Elena; De Luca, Roberto; Megna, Roberto; Maiolo, Mariangela; De Vito, Paolo; Gionfra, Fabio; Percario, Zulema Antonia; Borgatti, Monica; Gambari, Roberto; Davis, Paul J.; Lin, Hung-Yun; Polticelli, Fabio; et al. (Frontiers in Cell and Developmental Biology, 2021)
Interaction between thyroid hormones and the immune system is reported in the literature. Thyroid hormones, thyroxine, T4, but also T3, act non-genomically through mechanisms that involve a plasma membrane receptor αvβ3 integrin, a co-receptor for insulin-like growth factor-1 (IGF-1). Previous data from our laboratory show a crosstalk between thyroid hormones and IGF-1 because thyroid hormones inhibit the IGF-1-stimulated glucose uptake and cell proliferation in L-6 myoblasts, and the effects are mediated by integrin αvβ3. IGF-1 also behaves as a chemokine, being an important factor for tissue regeneration after damage. In the present study, using THP-1 human leukemic monocytes, expressing αvβ3 integrin in their cell membrane, we focused on the crosstalk between thyroid hormones and either IGF-1 or monocyte chemoattractant protein-1 (MCP-1), studying cell migration and proliferation stimulated by the two chemokines, and the role of αvβ3 integrin, using inhibitors of αvβ3 integrin and downstream pathways. Our results show that IGF-1 is a potent chemoattractant in THP-1 monocytes, stimulating cell migration, and thyroid hormone inhibits the effect through αvβ3 integrin. Thyroid hormone also inhibits IGF-1-stimulated cell proliferation through αvβ3 integrin, an example of a crosstalk between genomic and non-genomic effects. We also studied the effects of thyroid hormone on cell migration and proliferation induced by MCP-1, together with the pathways involved, by a pharmacological approach and docking simulation. Our findings show a different downstream signaling for IGF-1 and MCP-1 in THP-1 monocytes mediated by the plasma membrane receptor of thyroid hormones, integrin αvβ3.